2013
DOI: 10.1186/1471-2105-14-195
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying single nucleotide variant detection sensitivity in exome sequencing

Abstract: BackgroundThe targeted capture and sequencing of genomic regions has rapidly demonstrated its utility in genetic studies. Inherent in this technology is considerable heterogeneity of target coverage and this is expected to systematically impact our sensitivity to detect genuine polymorphisms. To fully interpret the polymorphisms identified in a genetic study it is often essential to both detect polymorphisms and to understand where and with what probability real polymorphisms may have been missed.ResultsUsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 30 publications
(53 reference statements)
2
68
1
Order By: Relevance
“…A limitation of our assay may be the use of a coverage threshold of 83 for variant detection. A recent study has reported that raising the coverage threshold to 133 markedly limited the number of missing variant calls (25). However, in the current study, a concordance rate of 100% was found between WES and PCR-based technology in microfluidic droplets in combination with NGS (in target genes that are present in the panel) using a coverage threshold of 83.…”
Section: Discussioncontrasting
confidence: 72%
“…A limitation of our assay may be the use of a coverage threshold of 83 for variant detection. A recent study has reported that raising the coverage threshold to 133 markedly limited the number of missing variant calls (25). However, in the current study, a concordance rate of 100% was found between WES and PCR-based technology in microfluidic droplets in combination with NGS (in target genes that are present in the panel) using a coverage threshold of 83.…”
Section: Discussioncontrasting
confidence: 72%
“…Whether or not another round of new sequencing technologies comes soon to replace current "next generation" sequencing technologies, their revolutionary impact is here to stay. Recently a huge impulse of NGS publications flooded into the scientific journals [1][2][3][4][5][6][7][8][9][10][11][12]. This is understandable as scientists try to make their mark in the NGS field.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative coverage counts (reported at depths 0-500), together with the genomic target size, were used to obtain the proportion of sites at each depth. The results of the product between estimated values for heterozygous sites from Meynert et al, (2013) and the proportion of sites, at each depth, were summed to get an overall SNP detection sensitivity per sample. The average of detection sensitivities per cohort was obtained by averaging the individual values across samples in each cohort.…”
Section: Discussionmentioning
confidence: 99%